Disruption of 5-Ht2a Receptor-Pdz Protein Interactions Alleviates Mechanical Hypersensitivity in Carrageenan-Induced Inflammation in Rats - Hernandez-Kunstmann, A (2013)
Despite common pathophysiological mechanisms, inflammatory and neuropathic pain do not respond equally to the analgesic effect of antidepressants, except for selective serotonin reuptake inhibitors (SSRIs), which show a limited efficacy in both conditions. We previously demonstrated that an interfering peptide (TAT-2ASCV) disrupting the interaction between 5-HT2A receptors and its associated PDZ proteins (e.g. PSD-95) reveals a 5-HT2A receptor-mediated anti-hyperalgesic effect and enhances the efficacy of fluoxetine (a SSRI) in diabetic neuropathic pain conditions in rats. Here, we have examined whether the same strategy would be useful to treat inflammatory pain. Sub-chronic inflammatory pain was induced by injecting ?-carrageenan (100 ?l, 2%) into the left hind paw of the rat. Mechanical hyperalgesia was assessed after acute treatment with TAT-2ASCV or/and fluoxetine (SSRI) 2.5 h after ?-carrageenan injection. Possible changes in the level of 5-HT2A receptors and its associated PDZ protein PSD-95 upon inflammation induction were quantified by Western blotting in dorsal horn spinal cord. Administration of TAT-2ASCV peptide (100 ng/rat, intrathecally) but not fluoxetine (10 mg/kg, intraperitoneally) relieves mechanical hyperalgesia (paw pressure test) in inflamed rats. This anti-hyperalgesic effect involves spinal 5-HT2A receptors and GABAergic interneurons as it is abolished by a 5-HT2A antagonist (M100907, 150 ng/rat, intrathecally) and a GABAA antagonist, (bicuculline, 3 ?g/rat, intrathecally). We also found a decreased expression of 5-HT2A receptors in the dorsal spinal cord of inflamed animals which could not be rescued by TAT-2ASCV injection, while the amount of PSD-95 was not affected by inflammatory pain. Finally, the coadministration of fluoxetine does not further enhance the anti-hyperalgesic effect of TAT-2ASCV peptide. This study reveals a role of the interactions between 5-HT2A receptors and PDZ proteins in the pathophysiological pathways of inflammatory pain and opens new perspectives in its control thanks to molecules disrupting 5-HT2A receptor/PDZ protein interactions. © 2013 Wattiez et al.